The Swedish fiscal policy council: Watchdog with a broad remit - Lars Calmfors (Center for Economic Studies and ifo Institute (CESifo), 2012)
The Swedish Fiscal Policy Council (FPC) set up in 2007 is one example of the recent international trend to create independent fiscal watchdogs. The FPC has established itself as an important participant in the Swedish economic policy discussion. The FPC has small resources and a broad remit including employment, growth, income distribution and monitoring of how well the government explains its policies in addition to evaluation of fiscal policy. The reason why it can work is that the FPC acts as a complement to other institutions. The interaction between fiscal policy and other policy areas as well as the possibility to exploit the council's expertise in several areas are arguments in favour of the broad mandate, but at the same time there could be a risk that interest is diverted away from fiscal issues. The FPC's experiences illustrate the time inconsistency issues involved in establishing a fiscal council: a government has an incentive to create such a body as a signal that it will pursue responsible and rational policies, but it also has an incentive to constrain the council's activities once government policies are criticised.
Keywords: H60; 330; fiscal councils; fiscal discipline; fiscal frameworks; Finanzpolitik; Wirtschaftspolitische Beratung; Öffentliche Finanzplanung; Öffentliche Finanzwirtschaft; Schweden